Coherence characterization of partially coherent flat-topped beam propagating through atmospheric turbulence - Kashani, F.D.; Alavinejad, M.; Ghafary, B. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
We study the change in the degree of coherence of a partially coherent flat-topped (PCFT) beam propagating through atmospheric turbulence. It is shown analytically that with a fixed set of source parameters and under a particular atmospheric turbulence model, a PCFT beam propagating through atmospheric turbulence reaches its maximum value of coherence after propagating a particular distance, and the effective width of the spectral degree of coherence also has its maximum value. This phenomenon is independent of the turbulence model used. We also study the effects of beam width values, the structure constant of turbulent media and the degree of coherence on effective width of spectral degree of coherence. The results are illustrated by numerically calculated curves.
Optica Applicata, Vol. 39, 2009, nr 2, s. 429-440
Keywords: optyka; partially coherent flat-topped beams (PCFT); atmospheric turbulence; degree of coherence; effective width of the spectral degree of coherence